Research on Influencing Factors of corporate financial risk based on LightBM-SHAP model: Differentiation analysis under different corporate nature - Cao, Renguang; Cao, Jing; Huang, Ting (Transactions on Economics, Business and Management Research, 2024)
With the deepening of economic globalization and the increasing complexity of enterprise operating environment, it is of great theoretical and practical significance to study the key factors affecting enterprise financial risk and their mechanisms for improving enterprise risk management level and market competitiveness. Based on the annual data of China's A-share listed companies from 2019 to 2023, this paper constructs A comprehensive evaluation index system of financial risk, and adopts entropy method to conduct a quantitative evaluation of corporate financial risk. Through the introduction of LightGBM model and Shapley value method, the paper conducts feature screening on the multi-dimensional factors that affect the financial risk of enterprises, and identifies the core indicators that are highly correlated with the financial risk. Then, from the Angle of enterprise nature, the paper discusses the mechanism of different influence of these indicators on financial risk in different enterprise types. The empirical results show that both financial and non-financial indicators have significant effects on the financial risk of enterprises, but the importance of these indicators is significantly different in different natures of enterprises, especially the influence of non-financial indicators in non-state-owned enterprises is more prominent. Based on the above research conclusions, this paper puts forward the corresponding policy suggestions, which provide a guiding reference for the financial risk management of enterprises.